2015
DOI: 10.1021/acsami.5b02122
|View full text |Cite
|
Sign up to set email alerts
|

KCN Chemical Etch for Interface Engineering in Cu2ZnSnSe4 Solar Cells

Abstract: The removal of secondary phases from the surface of the kesterite crystals is one of the major challenges to improve the performances of Cu2ZnSn(S,Se)4 (CZTSSe) thin film solar cells. In this contribution, the KCN/KOH chemical etching approach, originally developed for the removal of CuxSe phases in Cu(In,Ga)(S,Se)2 thin films, is applied to CZTSe absorbers exhibiting various chemical compositions. Two distinct electrical behaviors were observed on CZTSe/CdS solar cells after treatment: (i) the improvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 38 publications
4
46
0
1
Order By: Relevance
“…Furthermore, our procedure does not contain any wet chemical etching step, which is generally used for removing secondary phases and/or improving the absorber surface. [13][14][15] These results demonstrate that as-grown kesterite absorbers can still perform at high-efficiency levels without additional process steps.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, our procedure does not contain any wet chemical etching step, which is generally used for removing secondary phases and/or improving the absorber surface. [13][14][15] These results demonstrate that as-grown kesterite absorbers can still perform at high-efficiency levels without additional process steps.…”
Section: Methodsmentioning
confidence: 74%
“…It is essential to underline that we apply only a facile one‐stage annealing approach, which does not require any complex temperature profile or any low‐temperature post‐annealing step. Furthermore, our procedure does not contain any wet chemical etching step, which is generally used for removing secondary phases and/or improving the absorber surface . These results demonstrate that as‐grown kesterite absorbers can still perform at high‐efficiency levels without additional process steps.…”
Section: Resultsmentioning
confidence: 86%
“…Although lower temperatures might be needed in the case of a thin film compound, other techniques might need to be envisaged to lower the temperature (and duration) of the post‐annealing treatment, such as the use of additives (i.e., halide compounds); solution based sulfurization techniques such as using 3‐mercaptopropionic acid as sulfur source and solvent could also be envisaged; 2) The review of the synthesis methods of the chalcogenide ABX 3 compounds have also shown that, as for most ternary compound, a slight deviation from the stoichiometric compound and/or an inadequate processing temperature will lead to the formation of secondary phases; depending on their location and their nature (i.e., conductivity, bandgap, etc. ), such secondary phases can have either a benign or a detrimental effect on the performance of thin film solar cells; a selective etching process done after the absorber processing can be envisaged to remove the secondary phases, as in the case of CuSe secondary phase in CIGS absorber that are etched by KCN treatment or alternatives . Further calculations might also be needed to determine the tolerance of the ABX 3 structure to sub‐stochiometric composition; 3) It is likely that the structure of the ABX 3 solar cell will differ from the standard structures of MAPI perovskite PV devices, due to the requirement of the processing conditions of the ABX 3 thin film; for example, the TiO 2 thin film usually used as ETL in the n‐i‐p structure would be converted into TiS 2 (or TiSe 2 ) during the sulfurization (selenization) step if used underneath the precursor thin film; Furthermore, the band alignment at the interface surrounding the absorber will also need to be adapted to the band structure of the absorber; therefore, the full solar cell structure will need to be redefined, depending on the absorber properties, based either on the n–i–p or the p–n structure concepts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interface defects are inevitable and play an essential role in device operation in practice. [157][158][159] As a terminal of periodical microcrystals which constitute the absorber layer, the surface usually has different chemical composition from the bulk, which consequently constructs a different defects structure on the surface of the absorber layer. For example, a Cu-depleted surface is commonly observed in generally adopted Cu-poor CIGS films.…”
Section: Engineering the Interface Defects And Band Bendingmentioning
confidence: 99%